Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan Dan Keputusan Investasi Terhadap Nilai Perusahaan - Arum Ludianingsih; Gendro Wiyono; Ratih Kusumawardhani (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Companies need funds to finance their operational activities, therefore a company must be able to attract investors to be interested in investing their capital. The high and low value of the company can be an attraction for investors. In addition to reflecting current conditions, company value can also describe the company's prospects in the future. Because it is important to do a research on what factors can have an influence on the value of the company. This study aims to analyze the effect of profitability, liquidity, firm size and investment decisions on firm value. The study was conducted on banks listed on the Indonesia Stock Exchange in 2018-2020, the sampling method used a purposive sampling technique. The analytical technique used is multiple linear regression analysis with the help of the SPSS program. The results of this study indicate that the variables of profitability, liquidity and investment decisions have a positive and significant effect on firm value. While the firm size variable has a negative and insignificant effect on firm value. Keywords: firm value, profitability, liquidity, firm size, investment decisions